2008
DOI: 10.1126/science.1149016
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Anoxia in the California Current Large Marine Ecosystem

Abstract: Eastern boundary current systems are among the world's most productive large marine ecosystems. Because upwelling currents transport nutrient-rich but oxygen-depleted water onto shallow seas, large expanses of productive continental shelves can be vulnerable to the risk of extreme low-oxygen events. Here, we report the novel rise of water-column shelf anoxia in the northern California Current system, a large marine ecosystem with no previous record of such extreme oxygen deficits. The expansion of anoxia highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
420
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 510 publications
(477 citation statements)
references
References 7 publications
10
420
1
2
Order By: Relevance
“…N 2 O production is enhanced in areas where oxygen levels are depleted and nitrate fuels denitrification. These conditions are combined in upwelling areas and it has been suggested that the global expansion of hypoxic/ anoxic zones (Chan et al, 2008) is leading to increased production of N 2 O and the accumulation of this radiatively active trace gas in the atmosphere (Naqvi et al, 2000).…”
Section: Impacts Of the Oceans On Climate Change 47mentioning
confidence: 99%
“…N 2 O production is enhanced in areas where oxygen levels are depleted and nitrate fuels denitrification. These conditions are combined in upwelling areas and it has been suggested that the global expansion of hypoxic/ anoxic zones (Chan et al, 2008) is leading to increased production of N 2 O and the accumulation of this radiatively active trace gas in the atmosphere (Naqvi et al, 2000).…”
Section: Impacts Of the Oceans On Climate Change 47mentioning
confidence: 99%
“…Starfish and mussels died, and rockfish and other mobile fish fled the hypoxic zone, which grew to 3,000 square kilometres (ref. 2).…”
Section: Deep Troublementioning
confidence: 99%
“…When dissolved oxygen is minimized, widespread mortality 11,12 or avoidance 13 of affected areas can result. OMZs in the eastern tropical seas represent the largest contiguous areas of naturally occurring hypoxia 9 in the world's oceans.…”
mentioning
confidence: 99%